2002
DOI: 10.1097/01.asn.0000018402.33620.c7
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression Pattern of Polycystin-2 in Acute and Chronic Renal Tubular Diseases

Abstract: Abstract. Polycystin-2 represents one of so far two proteins found to be mutated in patients with autosomal-dominant polycystic kidney disease. Evidence obtained from experiments carried out in cell lines and with native kidney tissue strongly suggests that polycystin-2 is located in the endoplasmic reticulum. In the kidney, polycystin-2 is highly expressed in cells of the distal and connecting tubules, where it is located in the basal compartment. It is not known whether the expression of polycystin-2 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Immunohistochemistry studies using staged mouse embryos indicated that PC2 expression is developmentally regulated and that this regulation is important for embryo development [ 47 ]. In adult mice, PC2 was also reported to be markedly up-regulated by renal ischaemic injury [ 48 50 ], indicating the importance of PC2 for the recovery from ischaemia. Studies of PC2-dependent ADPKD in mouse model also showed that both PC2 knock-out and knock-in mice develop typical renal cysts and an increase in cell proliferation and apoptosis, which are reflective of human ADPKD phenotypes [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry studies using staged mouse embryos indicated that PC2 expression is developmentally regulated and that this regulation is important for embryo development [ 47 ]. In adult mice, PC2 was also reported to be markedly up-regulated by renal ischaemic injury [ 48 50 ], indicating the importance of PC2 for the recovery from ischaemia. Studies of PC2-dependent ADPKD in mouse model also showed that both PC2 knock-out and knock-in mice develop typical renal cysts and an increase in cell proliferation and apoptosis, which are reflective of human ADPKD phenotypes [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rats from group 1 were sacrificed by whole body perfusion (see below) 2 wk after disease induction, the rats from group 2 after 5 wk, and those from group 3 after 10 wk. Twenty-four-hour urine collections were performed on day 10 (all animals), day 30 (animals from groups 2 and 3), and day 65 (rats from group 3); the excretion of total protein (Coomassie) and albumin (ELISA) was recorded as described previously (6).…”
Section: -22-3 Studymentioning
confidence: 99%
“…22 PKD1-haploinsufficient kidney cells, therefore, might be unable to achieve the required PC1 activity level when exposed to IR. Although studies on the ischemia/ PC2 relation have brought some potential contributions to this question, 23,24 the relationship between PC1 and IR is basically unknown. By coordinating cell planar polarity in renal tubules, PC1 might exert a protective effect after an ischemic insult.…”
mentioning
confidence: 99%